2010
DOI: 10.1016/j.ssi.2010.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature sintering of Ba(Zr0.8−xCexY0.2)O3−δ using lithium fluoride additive

Abstract: Lithium fluoride (LiF) was selected as a liquid phase sintering additive to lower the sintering temperature. The effects of LiF on the sinterability, microstructure, and electrochemical properties of Ba(Zr 0.8 − x Ce x Y 0.2 )O 3 − δ (0≤ x ≤ 0.4) (BZCYs) ceramics were investigated. Using LiF as an additive, high density BZCYs ceramics can be obtained at sintering temperatures 200-300°C lower than the usual 1700°C with much shorter soaking time.Nuclear reaction investigations showed no lithium and a small amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…In the recent study by Tsai et al [22], nuclear reaction analysis (which is sensitive to elemental concentration) showed negligible residue of Li in 7 wt.% LiF-added BZCY622 solid ceramic after sintering at 1400°C for various dwell times [22]. The 7 wt.% LiF-addition does not reduce conductivity, but rather slightly improves the total Post XRD spectra of LiF-added BZCY712 and BZCY622 (a and d) after calcining at 1200°C in air for 5 h, (b and e) after subsequent exposure to CO 2 at 850°C for previously calcined powders at 1200°C for 5 h, and (c and f) after calcining at 1400°C in air for 5 h. "+" and "#" indicate BaCO 3 and Y 2 O 3 -like structure, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In the recent study by Tsai et al [22], nuclear reaction analysis (which is sensitive to elemental concentration) showed negligible residue of Li in 7 wt.% LiF-added BZCY622 solid ceramic after sintering at 1400°C for various dwell times [22]. The 7 wt.% LiF-addition does not reduce conductivity, but rather slightly improves the total Post XRD spectra of LiF-added BZCY712 and BZCY622 (a and d) after calcining at 1200°C in air for 5 h, (b and e) after subsequent exposure to CO 2 at 850°C for previously calcined powders at 1200°C for 5 h, and (c and f) after calcining at 1400°C in air for 5 h. "+" and "#" indicate BaCO 3 and Y 2 O 3 -like structure, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…"□" represents possibly high-cerium BZCY. conductivity of BZCY (x = 0.0-0.4) ceramics measured at 700°C in a water saturated 4% H 2 + 96% Ar atmosphere [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged sintering at high temperatures, although may result in a product with higher density and larger grain sizes but often also result in lowered bulk conductivities because of barium deficiency and creation of cation non-stoichiometry in the sintered compound [17,18]. Recently different processing approaches such as reactive sintering, introduction of sintering aids such as ZnO, CuO, NiO or LiF or their combination were introduced as promising methods for fabrication of barium zirconate-based compounds with both high bulk conductivity and large grains, leading to a high total conductivity [19][20][21][22][23][24]. However, the stability of the transition metal oxides under reducing atmosphere and their impact on the ionic transfer is under question and has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [19] studied the effect of sintering temperature in Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3Àd membranes for O 2 separation. Tsai et al [20] worked on BaCeYO membrane and showed good results for H 2 separation. However, there are no major reports about the effect of the sintering parameters, such as temperature and dwell time, on the microstructure of membranes and their influence on permeation flux in hydrogen separation, and therefore it seems to be necessary to focus our attention in this field.…”
Section: Introductionmentioning
confidence: 99%